Smart Co2 detector prototype development to enhance the efficiency of ventilation system in a building - Mohd Zin, Mohd Hanif; Syed Ismail, Sharifah Norkhadijah; Karuppiah, Karmegam (Tehran University of Medical Sciences, 2016)
Background: This study developed a smart CO2 detector, which attach to the general ventilation system to reduce the gas level. Methods: Indoor air quality measurement was performed in five selected rooms between January 2015 to February 2015 using TSI Q-Trak™ Indoor Air Monitor 7575. The perceived indoor air quality conditions was gathered using questionnaires adopted from the Industrial Code of Practice (ICOP) of Indoor Air Quality 2010 by the Department of Occupational Safety and Health (DOSH). The AutoCad 2010 and Soldworks 2011 software were used to design and develop the CO2 detector. Results: The highest concentration of CO2 was determined in the occupied tutorial room (1435 ± 62.6 ppm) followed by lecture hall 3 (1337.67± 14.6 ppm) and lecture hall 4 (1109 ± 4.0 ppm). The highest temperature was recorded in occupied tutorial room (29 ± 0.3 ºC) while the highest relative humidity was recorded in occupied lecture hall 4 (76 ± 3.1 %). All of these values exceed the ICOP standard level. Varying room temperature was the most common problem reported (n = 34, 22.7%) followed by unpleasant odors (n = 22, 14.7%) and drafty (n = 21, 14%). The CO2 sensor attached to the general ventilation system triggers the ventilation system to regulate the air into the building more efficiently when CO2 exceeds 800 ppm. The detector may stop the system when the pollutants level is back to normal. Conclusion: The CO2 detector system helps to regulate the air movement and reduce the CO2 level.